Allosteric Modulation of Muscarinic Acetylcholine Receptors - Jakubík, Jan; El-Fakahany, Esam E (Pharmaceuticals (Basel, Switzerland), 2010)
An allosteric modulator is a ligand that binds to an allosteric site on the receptor and changes receptor conformation to produce increase (positive cooperativity) or decrease (negative cooperativity) in the binding or action of an orthosteric agonist (e.g., acetylcholine). Since the identification of gallamine as the first allosteric modulator of muscarinic receptors in 1976, this unique mode of receptor modulation has been intensively studied by many groups. This review summarizes over 30 years of research on the molecular mechanisms of allosteric interactions of drugs with the receptor and for new allosteric modulators of muscarinic receptors with potential therapeutic use. Identification of positive modulators of acetylcholine binding and function that enhance neurotransmission and the discovery of highly selective allosteric modulators are mile-stones on the way to novel therapeutic agents for the treatment of schizophrenia, Alzheimer's disease and other disorders involving impaired cognitive function.
Keywords: allosteric modulation; muscarinic acetylcholine receptors; schizophrenia; Alzheimer’s disease